Super-ionic metal organic framework, preparation method and application thereof, solid electrolyte composite membrane and application thereof
By introducing Li2SO4 permeation method to construct superion state Li-MOF-SO4, the problems of uneven loading, low diffusion rate and poor structural stability in lithium-ion conductors are solved, and efficient and stable lithium-ion conductivity and green preparation technology are achieved, which is suitable for all-solid lithium metal batteries.
Patent Information
- Application Number
- CN202510587291.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-08
- Publication Date
- 2025-07-18
AI Technical Summary
The existing metal organic frames have problems such as uneven loading of lithium ion, low ion diffusion rate, poor structural stability and complex process in lithium ion conductors, especially when used in flexible devices, which are costly and inapplicable.
Lithium ions are uniformly introduced into MOF through Li2SO4 permeation method to construct superion Li-MOF-SO4, and a superionic metal organic framework is prepared by low-temperature solution method, combining the synergistic action of sulfonic acid groups and high ion migration number design to improve ion conductivity and structural stability.
The ionic conductivity is significantly improved to 5.3×10-3S/cm at room temperature, and the capacity retention rate exceeds 90% after 1,000 cycles. The process is green and efficient, and there is no need for complicated post-treatment.
Smart Images

Figure CN120329561A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solid electrolytes, and particularly to a superionic metal-organic framework and its preparation method and application, a solid electrolyte composite film and its application. Background Art
[0002] Metal-organic frameworks (MOFs) have potential in lithium-ion conductors due to their ordered nanopores, but there are the following problems: uneven lithium-ion loading: traditional physical mixing of lithium salts (such as LiTFSI) leads to pore blockage and low ion diffusion rate (usually <10 -4 S / cm); poor structural stability: post-synthetic modification (such as ion exchange) easily destroys the MOF crystal structure, and the capacity decays rapidly during cycling; complex process: high-temperature calcination or strong acid treatment increases production costs and is not suitable for flexible devices. Summary of the Invention
[0003] In order to solve the above problems, the present invention provides a superionic metal-organic framework and its preparation method and application, a solid electrolyte composite film and its application. The present invention uniformly introduces lithium ions into MOF (such as UiO-66) by the Li2SO4 infiltration method to construct superionic Li-MOF-SO4. The ionic conductivity of the superionic metal-organic framework provided by the present invention is significantly improved: reaching 5.3×10 -3 S / cm (EIS test) at room temperature, the structural stability is enhanced: the capacity retention rate >90% after 1000 cycles, and the process is green and efficient: a low-temperature solution method without complex post-treatment.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The present invention provides a preparation method of a superionic metal-organic framework, comprising the following steps:
[0006] 1) Mix zirconium chloride, terephthalic acid, and dimethylformamide to obtain a mixed solution;
[0007] 2) Allow the mixed solution obtained in step 1) to stand for reaction, centrifuge to obtain a precipitate, and dry the precipitate to obtain a MOF precursor;
[0008] 3) Disperse the MOF precursor obtained in step 2) in methanol, then stir and mix with lithium sulfate, and wash and dry the filtered solid in sequence to obtain a superionic metal-organic framework.
[0009] Preferably, the mass ratio of zirconium chloride, the mass of terephthalic acid, and the volume of dimethylformamide in step 1) is 2g:1.5g:20mL;
[0010] The mixing is carried out by ultrasonic mixing for 30 min.
[0011] Preferably, the conditions for the static reaction in step 2) include: temperature is 120 °C and time is 24 h;
[0012] The conditions for the centrifugation include: rotation speed is 8000 rpm and time is 10 min;
[0013] The conditions for the drying include: vacuum drying at 80 °C for 12 h.
[0014] Preferably, the mass ratio of the MOF precursor in step 3) to the volume of methanol and the mass of lithium sulfate is 1 g: 30 mL: 1.5 g;
[0015] The time for the stirring and mixing is 24 h;
[0016] Wash with methanol three times;
[0017] The conditions for the drying include: vacuum drying at 60 °C for 24 h.
[0018] The present invention also provides a superionic metal-organic framework prepared by the preparation method described in the above technical solution.
[0019] The present invention also provides the application of the superionic metal-organic framework described in the above technical solution in the preparation of a solid electrolyte composite membrane.
[0020] The present invention also provides a solid electrolyte composite membrane prepared from components with the following mass percentages: 20% of the superionic metal-organic framework described in the above technical solution 5, 50% of polyethylene oxide, 20% of lithium bis(trifluoromethanesulfonyl)imide, and 10% of silica.
[0021] The present invention also provides a preparation method of the solid electrolyte composite membrane described in the above technical solution, including the following steps: dissolving the superionic metal-organic framework, polyethylene oxide, lithium bis(trifluoromethanesulfonyl)imide, and silica in acetonitrile, and stirring for 24 h to obtain a slurry;
[0022] Casting the slurry into a film, and then vacuum drying at 60 °C for 12 h to obtain a solid electrolyte composite membrane;
[0023] The thickness of the film is 100 μm.
[0024] The present invention also provides the application of the solid electrolyte composite membrane described in the above technical solution in the preparation of an all-solid-state lithium metal battery.
[0025] The present invention also provides an all-solid-state lithium metal battery assembled from the solid electrolyte composite membrane, a positive electrode, and a negative electrode described in the above technical solution;
[0026] The positive electrode is LiNi 0.8 Co 0.1 Mn 0.1 O2, and the negative electrode is a lithium foil.
[0027] 1. Li2SO4 directional penetration process: Uniform loading of lithium ions in the MOF channels is achieved through a methanol solvent.
[0028] 2. Synergistic effect of sulfonic acid groups: SO4 2- Balances charges and broadens the ion transport channels.
[0029] 3. High ion transference number design: Synergistic conduction mechanism of Li-MOF-SO4 (superionic metal-organic framework) and PEO composite membrane.
[0030] Advantages of the present invention:
[0031] Structure characterization of the superionic metal-organic framework: XRD and N2 adsorption prove that the MOF channels remain intact after Li+ loading (pore size distribution 2.1 ± 0.2 nm).
[0032] Battery performance: The LiFePO4 / Li battery (all-solid-state lithium metal battery) cycles 500 times at 1C, and the capacity retention rate is 91.5%. Description of the drawings
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the embodiments.
[0034] Figure 1 Synthesis schematic diagram of Li-MOF-SO4 (Li2SO4 penetrates into the UiO-66 channels, SO4 2- coordination effect);
[0035] Figure 2 XRD comparison before and after MOF modification (indicating crystal plane shift and unit cell parameter changes);
[0036] Figure 3 Schematic diagram of the lithium ion migration path (directional transport of Li + in the MOF channels);
[0037] Figure 4 Arrhenius curve of the ionic conductivity of the solid electrolyte membrane (activation energy reduced to 0.18 eV). Detailed implementation manners
[0038] The present invention provides a preparation method for a superionic metal-organic framework, including the following steps:
[0039] 1) Mix zirconium chloride, terephthalic acid, and dimethylformamide to obtain a mixed solution.
[0040] 2) Let the mixed solution obtained in step 1) stand for reaction, centrifuge to obtain a precipitate, and dry the precipitate to obtain a MOF precursor.
[0041] 3) Disperse the MOF precursor obtained in step 2) in methanol, then stir and mix it with lithium sulfate. Wash and dry the filtered solid in sequence to obtain a superionic metal-organic framework.
[0042] In the present invention, zirconium chloride is mixed with terephthalic acid and dimethylformamide to obtain a mixed solution. In the present invention, the mass ratio of zirconium chloride to terephthalic acid and the volume ratio of zirconium chloride to dimethylformamide are preferably 2 g:1.5 g:20 mL. In the present invention, the mixing is preferably carried out by ultrasonic mixing for 30 min.
[0043] In the present invention, the obtained mixed solution is allowed to stand for reaction, centrifuged to obtain a precipitate, and the precipitate is dried to obtain a MOF precursor. In the present invention, the conditions for the standing reaction preferably include: temperature of 120 °C and time of 24 h. In the present invention, the conditions for centrifugation preferably include: rotation speed of 8000 rpm and time of 10 min. In the present invention, the conditions for drying preferably include: vacuum drying at 80 °C for 12 h.
[0044] In the present invention, the obtained MOF precursor is dispersed in methanol, then stirred and mixed with lithium sulfate. The filtered solid is washed and dried in sequence to obtain a superionic metal-organic framework. In the present invention, the mass ratio of the MOF precursor to the volume of methanol and the mass of lithium sulfate is preferably 1 g:30 mL:1.5 g. In the present invention, the time for the stirring and mixing is preferably 24 h. In the present invention, it is preferably washed with methanol three times. In the present invention, the conditions for drying preferably include: vacuum drying at 60 °C for 24 h.
[0045] The present invention also provides a superionic metal-organic framework prepared by the preparation method described in the above technical solution.
[0046] The present invention also provides the application of the superionic metal-organic framework described in the above technical solution in the preparation of a solid electrolyte composite membrane.
[0047] The present invention also provides a solid electrolyte composite membrane, which is prepared from the following components by mass percentage: 20% of the superionic metal-organic framework described in the above technical solution, 50% of polyethylene oxide, 20% of lithium bis(trifluoromethanesulfonyl)imide, and 10% of silicon dioxide.
[0048] The present invention also provides a method for preparing the solid electrolyte composite film described in the above technical solution, including the following steps: dissolving the superionic metal-organic framework, polyethylene oxide, lithium bis(trifluoromethanesulfonyl)imide, and silicon dioxide in acetonitrile, stirring for 24 h to obtain a slurry; casting the slurry into a film (scraped with a 500-μm blade), and then drying it under vacuum at 60 °C for 12 h to obtain the solid electrolyte composite film; the thickness of the film is 100 μm.
[0049] The present invention also provides the application of the solid electrolyte composite film described in the above technical solution in the preparation of all-solid-state lithium metal batteries.
[0050] The present invention also provides an all-solid-state lithium metal battery, which is assembled from the solid electrolyte composite film, a positive electrode, and a negative electrode described in the above technical solution 7; the positive electrode is LiNi 0.8 Co 0.1 Mn 0.1 O2, and the negative electrode is a lithium foil. The present invention has no special limitation on the assembly method of the all-solid-state lithium metal battery, and those skilled in the art can assemble it by using a conventional assembly method.
[0051] To further illustrate the present invention, the present invention will be described in detail below in conjunction with embodiments, but they cannot be construed as limiting the protection scope of the present invention.
[0052] Example 1
[0053] 1. Synthesis of MOF precursor (UiO-66), steps:
[0054] 1) Dissolve ZrCl4 (2 g) and terephthalic acid (1.5 g) in DMF (20 mL), and ultrasonically disperse for 30 minutes;
[0055] 2) Let it stand and react at 120 °C for 24 hours, centrifuge (8000 rpm for 10 min) to collect white crystals, wash with DMF 3 times, and vacuum dry at 80 °C for 12 h.
[0056] Synthesize highly crystalline UiO-66 (BET specific surface area > 1200 m 2 / g) under mild conditions.
[0057] 2. Directional penetration of lithium ions (preparation of Li-MOF-SO4), steps:
[0058] 1) Disperse UiO-66 (1 g) in methanol (30 mL), add Li2SO4 (1.5 g), and stir for 24 hours;
[0059] 2) Filter, wash with methanol 3 times, and vacuum dry at 60 °C for 24 h to obtain Li-MOF-SO4 powder.
[0060] Selective Permeation: Li+ coordinates with sulfonic acid groups through the pores of MOF, avoiding pore blockage (XRD shows that the lattice parameters only expand by 2%).
[0061] XRD Testing and Data Collection
[0062] Instruments and Parameters:
[0063] Use an X-ray diffractometer (such as Bruker D8 Advance), Cu-Kα radiation Scanning range 5 - 50° (2θ), step size 0.02°, scanning speed 2° / min.
[0064] Sample Testing:
[0065] Perform XRD tests on the original MOF (UiO-66) and Li-MOF-SO4 respectively to obtain diffraction patterns.
[0066] Example Patterns:
[0067] Original MOF: The positions of the characteristic peaks are consistent with the standard UiO-66 pattern (such as 2θ ≈ 7.3°, 8.5°, 25.7°).
[0068] Li-MOF-SO4: The characteristic peaks are slightly shifted (such as 2θ ≈ 7.2°, 8.4°, 25.5°).
[0069] Step 3: Lattice Parameter Calculation
[0070] Use XRD analysis software:
[0071] Import XRD data into professional software (such as Jade, HighScore).
[0072] Calculate the unit cell parameters (a, b, c, α, β, γ) through Rietveld refinement or peak position fitting.
[0073] Lattice Parameters of the Original MOF:
[0074] Standard Unit Cell Parameters of UiO-66: α = β = γ = 90° (cubic crystal system).
[0075] Lattice Parameters of Li-MOF-SO4:
[0076] Refined Parameters: The percentage change is calculated as follows:
[0077] Change rate = (21.16 - 20.75) / 20.75 × 100% ≈ 2.0%.
[0078] Ion Transport Channel Optimization: SO4 2-As a charge balancing group, to improve the lithium ion transference number (t + = 0.78).
[0079] 3. Solid electrolyte composite film
[0080] Composition: 20 wt% Li-MOF-SO4, 50 wt% polyethylene oxide (PEO), 20 wt% lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and 10 wt% SiO2.
[0081] Preparation method:
[0082] 1) Dissolve the above components in acetonitrile and stir for 24 hours to form a homogeneous slurry.
[0083] 1) Cast the obtained slurry into a film (thickness after drying: 100 μm) and dry it under vacuum at 60 °C for 12 hours. Obtain a solid electrolyte composite film (Li-MOF-SO4 / PEO composite film).
[0084] Ionic conductivity: 5.3×10 -3 S / cm (25 °C, EIS test), which is 10 times higher than that of the traditional MOF / PEO composite film.
[0085] Preparation method of traditional MOF / PEO composite film
[0086] 1. Materials and reagents
[0087] MOF precursor: Taking unmodified UiO-66 as an example. Its synthesis method is similar to that described in the patent, that is, zirconium chloride (ZrCl4) reacts with terephthalic acid (H2BDC) in N,N-dimethylformamide (DMF) solvent for preparation.
[0088] Polyethylene oxide (PEO): Molecular weight is 600k (600,000 g / mol), and the purity requirement is greater than or equal to 99%.
[0089] Lithium salt: Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and the purity requirement is greater than or equal to 99.9%.
[0090] Solvent: Acetonitrile (CH3CN), and the purity requirement is greater than or equal to 99.8%.
[0091] 2. Preparation steps
[0092] 1. Preparation of MOF precursor (taking UiO-66 as an example):
[0093] Mix 2 grams of zirconium chloride and 1.5 grams of terephthalic acid with 20 milliliters of DMF.
[0094] Use ultrasonic dispersion for 30 minutes to uniformly disperse the solid in the solvent.
[0095] The mixture was allowed to stand and react at 20 °C for 24 hours.
[0096] After the reaction was completed, the precipitate was collected by centrifugation (centrifugation conditions: 8000 rpm, centrifugation for 10 minutes).
[0097] The collected precipitate was vacuum dried at 80 °C for 12 hours to obtain UiO-66 powder.
[0098] 2. Mixing MOF and PEO:
[0099] 1) Mix the components in the following mass ratios:
[0100] MOF (UiO-66): 20%
[0101] PEO: 50%
[0102] LiTFSI: 20%
[0103] SiO2 (silicon dioxide): 10% (this component is an optional addition, mainly to enhance the mechanical strength of the composite membrane).
[0104] 20 Add the above mixture to 30 milliliters (mL) of acetonitrile solvent.
[0105] 3) Stir for 24 hours until a homogeneous slurry is formed.
[0106] 3. Film-forming process:
[0107] 1) Cast and coat the prepared homogeneous slurry on a glass substrate.
[0108] 2) Control the coating thickness to be approximately 100 micrometers (μm).
[0109] 3) Vacuum dry the coated substrate at 60 °C for 12 hours to remove the solvent, and finally obtain a traditional MOF / PEO composite membrane.
[0110] 4. Performance characteristics (compared with the patent solution)
[0111] 1) Ionic conductivity:
[0112] Measured by electrochemical impedance spectroscopy (EIS) at 25 °C, the ionic conductivity was approximately 5.3×10 -4 S / cm.
[0113] This value is significantly lower than the conductivity in the patent solution (5.3×10 -3 S / cm), about 10 times lower.
[0114] 2) Lithium ion transference number (t + )
[0115] The measured lithium ion transference number (t + ) is about 0.2 - 0.3.
[0116] This value is significantly lower than 0.78 in the patent solution.
[0117] 3) Structural defect analysis:
[0118] Problems with unmodified MOF: The UiO-66 used is unmodified, and there is no pre-loaded lithium ions or other functional groups inside its pores, which results in limited transport paths for lithium ions inside the MOF and low efficiency.
[0119] Problems with simple mixing: Each component is only prepared into a composite membrane through simple physical mixing, lacking key process steps such as Li2SO4 infiltration adopted in the patent solution. This leads to the inability to form optimized and efficient ion transport channels inside the composite membrane.
[0120] Interface stability: The lithium metal symmetric battery stably cycles > 1000 hours at 0.5 mA / cm 2 .
[0121] BET specific surface area: 1150 m 2 / g (before modification) → 1050 m 2 / g (after modification).
[0122] Lithium ion transference number (t + ) : 0.78 (Bruce-Vincent method).
[0123] Assemble a battery with the Li-MOF-SO4 / PEO composite membrane, LiNi 0.8 Co 0.1 Mn 0.1 O2 cathode and lithium foil anode.
[0124] Cycling performance: The capacity retention rate is 91.5% after 500 cycles at 1C.
[0125] Rate performance: The discharge capacity at 2C is 85% of that at 0.2C.
[0126] Comparative Example 1
[0127] Use acetonitrile as a solvent to replace methanol
[0128] Experimental purpose: Verify the effect of using acetonitrile for Li2SO4 infiltration modification of UiO-66.
[0129] Steps:
[0130] 1. Disperse 1 g of UiO-66 in 30 mL of acetonitrile.
[0131] 2. Add 1.5 g of Li2SO4.
[0132] 3. Stir for 24 hours at room temperature.
[0133] 4. Filter to obtain the solid product.
[0134] 5. Wash the solid 3 times with acetonitrile.
[0135] 6. Vacuum dry at 80 °C for 12 hours to obtain the product labeled Li-MOF-SO4.
[0136] Performance test results:
[0137] 1. Ionic conductivity: 2.1×10 -3 S / cm at 25 °C.
[0138] 2. Cycling stability: After 500 cycles, the capacity retention rate drops to 75%.
[0139] 3. XRD analysis: The results show that partial collapse of the MOF pores occurs (the unit cell parameter changes by +8%), indicating a decrease in structural stability.
[0140] Comparative Example 2
[0141] Use ethanol as a solvent to replace methanol
[0142] Experimental purpose: To verify the effect of using ethanol for Li2SO4 infiltration modification of UiO-66.
[0143] Steps:
[0144] 1. Disperse 1 g of UiO-66 in 30 mL of ethanol.
[0145] 2. Add 1.5 g of Li2SO4.
[0146] 3. Stir for 24 hours at room temperature.
[0147] 4. Filter to obtain the solid product.
[0148] 5. Wash the solid 3 times with ethanol.
[0149] 6. Vacuum dry at 60 °C for 12 hours to obtain the product labeled Li-MOF-SO4.
[0150] Performance test results:
[0151] 1. Ionic conductivity: 3.8×10 -3 S / cm at 25 °C.
[0152] 2. Cycling stability: After 800 cycles, the capacity retention rate is 82%.
[0153] 3. SEM observation: The results show that microcracks appear on the surface of the MOF, suggesting that there may be certain structural damage.
[0154] As can be seen from these three examples: The Li-MOF-SO4 material obtained by using methanol (Example 1) as the solvent for Li2SO4 infiltration modification has the highest ionic conductivity and the best cycle stability, and it is inferred from other information (such as the XRD data in the table) that its structure is maintained best (the change in unit cell parameters is only +2%). The performance of the material obtained by using ethanol (Comparative Example 2) is second, but microcracks are observed by SEM. The performance of the material obtained by using acetonitrile (Comparative Example 1) is the worst, with a significant decrease in ionic conductivity, poor cycle stability, and XRD showing partial collapse of the structure. These comparative experiments are designed to prove that methanol is the optimal solvent choice for this specific Li2SO4 infiltration modification of UiO-66, and can obtain the solid electrolyte material with the best performance and the most stable structure. This supports the technical advantages of the patent solution.
[0155] Although the above embodiments have described the present invention in detail, they are only a part of the embodiments of the present invention, rather than all embodiments. People can also obtain other embodiments based on this embodiment without creative efforts, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A preparation method of a superionic metal-organic framework, characterized in that, It includes the following steps: 1) Mix zirconium chloride with terephthalic acid and dimethylformamide to obtain a mixed solution; 2) Let the mixed solution obtained in step 1) stand for reaction, centrifuge to obtain a precipitate, and dry the precipitate to obtain a MOF precursor; 3) Disperse the MOF precursor obtained in step 2) in methanol, then stir and mix it with lithium sulfate, and wash and dry the filtered solid in sequence to obtain a superionic metal-organic framework.
2. The preparation method according to claim 1, characterized in that, In step 1), the mass ratio of zirconium chloride to terephthalic acid and the volume ratio of zirconium chloride to dimethylformamide are 2 g:1.5 g:20 mL; The mixing is carried out by ultrasonic mixing for 30 min.
3. The preparation method according to claim 1, characterized in that, The conditions for the standing reaction in step 2) include: temperature is 120 °C and time is 24 h; The conditions for the centrifugation include: rotation speed is 8000 rpm and time is 10 min; The conditions for the drying include: vacuum drying at 80 °C for 12 h.
4. The preparation method according to claim 1, wherein, In step 3), the mass ratio of the MOF precursor to the volume of methanol and the mass of lithium sulfate is 1 g:30 mL:1.5 g; The time for the stirring and mixing is 24 h; Wash with methanol 3 times; The conditions for the drying include: vacuum drying at 60 °C for 24 h.
5. A superionic metal-organic framework prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the superionic metal-organic framework according to claim 5 in the preparation of a solid electrolyte composite membrane.
7. A solid electrolyte composite membrane, characterized in that, It is prepared from components with the following mass percentages: 20% of the superionic metal-organic framework according to claim 5, 50% of polyethylene oxide, 20% of lithium bis(trifluoromethanesulfonyl)imide, and 10% of silica.
8. A method for preparing the solid electrolyte composite membrane according to claim 7, characterized in that, It includes the following steps: Dissolve the superionic metal-organic framework, polyethylene oxide, lithium bis(trifluoromethanesulfonyl)imide, and silica in acetonitrile and stir for 24 h to obtain a slurry; Cast the slurry into a film, and then vacuum dry it at 60 °C for 12 h to obtain a solid electrolyte composite membrane; The thickness of the film is 100 μm.
9. Use of the solid electrolyte composite membrane according to claim 7 in the preparation of an all-solid-state lithium metal battery.
10. A all-solid-state lithium metal battery, characterized in that, It is assembled from the solid electrolyte composite membrane according to claim 7, a positive electrode, and a negative electrode; The positive electrode is LiNi 0.8 Co 0.1 Mn 0.1 O2, and the negative electrode is a lithium foil.